Modern optical engineering : t - Smith, Warren J. (McGraw Hill, 2008)
Written by the renowned optical scientist Warren J. Smith, this state-of-the-art guide provides unsurpassed coverage of image formation, basic optical devices, image evaluation, fabrication and testing methods, and more. Comprehensive and up-to-date, Modern Optical Engineering features: The latest information on optical engineering theory, design, and practice ; Over 150 detailed illustrations ; New to this edition: new coverage of ray tracing, optical system design, and third-order aberration theory; new lens designs; new optical design software; and new problems and exercises ;